Differences in performance indicators between u'16 male winners and losers handball teams, based on goal difference - Francisco Javier Sáez Blázquez; Javier García Rubio; Antonio Antúnez Medina; Andrea Valle Blanco; Sebastián Feu Molina (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The aim of this study was to identify performance indicators to differentiate between winning and losing u'16 men handball teams, based on the final score differences. We analyzed 46 games from the 2011 Spanish Championship of Regional Teams. The analysis was developed with specific software SPSS17.0 for Windows. A cluster analysis was carried out based on the final score differences. Normality, homoscedasticity and randomness tests were applied; based on these results, it was carried out a student t test for independent samples or the Mann-Whitney test. The statistical analysis showed differences in Offensive Efficacy Coefficient (OEC) , Offensive Realization Coefficcient (ORC),  6m goals, total losses, total saves made, 6m failed launches and error-pass reception. In those games where the differences of goals were greater, the number of performance indicators that differentiate winners from losers increased. The effectiveness of 6 meters, the turnovers and the goalkeeper performance were crucial to victory. Key words: Handball, Performance indicators, Learning ages, Victory/Defeat.